Number 1 - Bird, John
Number 1 covers basic arithmetic, decimals, fractions, common calculations and indices. The underlying theory of all subjects are covered in brief, and 21 virtual laboratories provide good visual models for learning the mathematical concepts and procedures, as well as providing an opportunity for students to learn through investigation. As with all Matrix Mathematics products there are scores of worked examples and questions, including worked solutions, and the Virtual Laboratories give potential for a limitless number of further worked examples. Summary worksheets are also included which can be used as a framework for assessment.